C/EBPα in normal and malignant myelopoiesis - Friedman, Alan D. (International journal of hematology, 2015)
CCAAT/enhancer binding protein α (C/EBPα) dimerizes via its leucine zipper (LZ) domain to bind DNA via its basic region and activate transcription via N-terminal trans-activation domains. The activity of C/EBPα is modulated by several serine/threonine kinases and via sumoylation, its gene is activated by RUNX1 and additional transcription factors, its mRNA stability is modified by miRNAs, and its mRNA is subject to translation control that affects AUG selection. In addition to inducing differentiation, C/EBPα inhibits cell cycle progression and apoptosis. Within hematopoiesis, C/EBPα levels increase as long-term stem cells progress to granulocyte–monocyte progenitors (GMP). Absence of C/EBPα prevents GMP formation, and higher levels are required for granulopoiesis compared to monopoiesis. C/EBPα interacts with AP-1 proteins to bind hybrid DNA elements during monopoiesis, and induction of Gfi-1, C/EBPε, KLF5, and miR-223 by C/EBPα enables granulopoiesis. The CEBPA ORF is mutated in approximately 10 % of acute myeloid leukemias (AML), leading to expression of N-terminally truncated C/EBPαp30 and C-terminal, in-frame C/EBPαLZ variants, which inhibit C/EBPα activities but also play additional roles during myeloid transformation. RUNX1 mutation, CEBPA promoter methylation, Trib1 or Trib2-mediated C/EBPαp42 degradation, and signaling pathways leading to C/EBPα serine 21 phosphorylation reduce C/EBPα expression or activity in additional AML cases.